Expert System With Certainty Factor For Early Diagnosis Of Red Chili Peppers Diseases - Fahrul Agus; Hernanda Eka Wulandari; Indah Fitri Astuti (Universitas Dian Nuswantoro and IndoCEISS, 2017)
Red chili peppers (Capsicum annuum L.) plants classified as fruit and vegetables spices (herbs), that almost all people consume it for everyday purposes. Not only used for household consumption, but also used in various industries as a raw material. Utilization as raw materials in various industry makes red chili as vegetable crops of high economic value and has a great prospect. But its diseases are complex enough for causing farmers hard to diagnose and resulted in reduced production levels. One solution to this problem is the establishment of an expert system that can help farmers to diagnose major diseases of red pepper plant in a practical and accurate. The purpose of this research is to make the application of expert systems for diagnosing diseases of red chili. This application uses forward chaining to diagnose disease and calculate the value of possibilities with Certainty Factor. This method is to prove whether a fact that certainly would not have been shaped or metrics that are typically used in an expert system. This method is suitable for expert systems to diagnose something uncertain. Certainty Factor expressed confidence in an event or factual hypothesis based on evidence or expert judgment. The results of research is in the form of an expert system application that can diagnose diseases of red pepper plants with enough accuracy and can help in overcoming the problem of crop failure. Based on the data taken from tests performed in this study, the system can diagnose red chili plant disease with high accuracy.